FACTORS AFFECTING LIFE EXPECTANCY IN KUANSING REGENCY - Riviolla Nandita; Neng Murialti; M. Fikri Hadi (Yayasan Wayan Marwan Pulungan, 2025)
This research was conducted in Kuansing Regency, Riau Province with the purpose of this study is to determine the effect of Economic Growth, Average Length of Schooling and Health Facilities on Life Expectancy in Kuansing Regency. This type of research uses a descriptive analysis method with a quantitative approach. Based on the results of the study, it can be concluded that the Rate of Economic Growth/GDP, Average Length of Schooling and Health Facilities on Life Expectancy experienced significant growth on Life Expectancy in Kuansing Regency. We can see in the R2 Determination of 0.887% this also shows the contribution of the influence of the independent variable on the dependent variable of 88.7% where the range value is at 0.80 - 1,000 which means it is very strong on the Rate of Economic Growth, Average Length of Schooling and Health Facilities in Kuansing Regency and Based on the Problem Formulation that the influence of the relationship between the Rate of Economic Growth on Life Expectancy is very significant, we can see in the T Test Sig value of 0.001 meaning that the Rate of Economic Growth has a Sig influence on the Life Expectancy Variable in Kuansing Regency. Meanwhile, the influence of Average Length of Schooling on Life Expectancy is equally significant on Life Expectancy in Kuansing Regency, while the influence of Health Facilities on the T-Test decreased by 0.096, which means that the Health Facilities variable does not have a significant influence on Life Expectancy.